Evaluasi Kemampuan dan Kesesuaian Lahan untuk Budidaya Kopi Arabika di Desa Jayagiri, Lembang, Bandung Barat, Jawa Barat - Hafizh Marianto; Mujiyo Mujiyo; Sutarno Sutarno; Lidya Zaela Wijaya; Khoerunnisa Amaliah Syamsuddin; Balina Dita Eisya Prashanti Nugroho (Universitas Sebelas Maret, 2022)
Arabica Coffee Cultivation in Jayagiri Village as a Result of Land Suitability Evaluation Assessment. Jayagiri Village, Lembang District, West Bandung Regency, West Java has the agricultural sector as its economic main sector. This village is located at an altitude of 1,312-2,084 m above sea level and has a plantation area of 23 ha. Plant commodities other than vegetables need to be developed at that location, therefore information on land suitability is needed. One commodity that has a high potential to be developed is Arabica coffee, while information relating to the characteristics and suitability of land for this commodity needs to be known. This activity aims to determine the land suitability class for Arabica coffee and how to improve the limiting factors at the research site. Evaluation of land suitability is carried out based on procedures from BPPS for Agricultural Land, Ministry of Agriculture. The research stages include pre-survey activities, making SPT, taking soil samples, making representative pedons, and analyzing samples. Data analysis was carried out using the matching method to determine the land suitability class and its limiting factors. The results of the activity show that the land suitability class in Jayagiri Village is included in the marginal suitability class (S3). The limiting factor of land suitability in the area is the high slope and low availability of nutrients. Efforts that can be made to improve the land suitability class, as well as the limiting factor, are by conserving terraces and fertilizing both organically and inorganically.